Reducing waste in the convection industry by lean six sigma and DMAIC implementation approach - Faishal Muhammad; Krisna Ratih Dewita; Maharani Khoirunnisa (BIO Web of Conferences)
Convection industries are always required to improve quality. The ABC convection industry faces several problems in the production process, such as waste product defects of up to 10%, waste over-processing, and transportation waste. This research aims to reduce the occurrence of waste in The ABC production process. The method used in this research is Lean Six Sigma and the DMAIC approach (define, measure, analyze, improve, and control), which have been proven to reduce waste. In the DMAIC stages, the fishbone diagram is used in the analysis stage to find the root of the problem, while the 5W+1H method is used in the improvement stage to provide recommendations for improvement. The improvements implemented include re-layout the sewing workstation, installing a partition on the sewing table, and adding tools such as material measuring stickers and grouping patterns based on models at the patterning and cutting workstations. The workstation space was moved to the same building to eliminate transportation waste. After the improvement, the sigma level calculation results showed an increase of 10%, from a sigma level of 3.5 to 3.9 sigma.